Effect of Laser Distance Measurement for Fatigue Crack Detection on Aluminium Plate Using Laser Doppler Vibro-Meter - Tino Hermanto; Arya Rudi Nasution; Hermansyah Hermasnyah; Yopan Rahmad Aldori; Ruztamreen Bin Jenal; Abd Rahman Bin Dullah; Adly Zulqarnain bin Mohamad; Habib Satria (Journal of Applied Engineering and Technological Science (JAETS), 2024)
Fatigue cracks can occur because the material is unable to withstand the load applied repeatedly. A nonlinear vibroacoustic method was introduced to overcome this problem. This is because this method is one of the best solutions because it is suitable for detecting fatigue cracks which is sensitive enough to detect small cracks. The aim of the research is to determine the effect of laser distance measurements on fatigue crack detection using the vibroacoustic method. Therefore, there are steps or procedures that include test object preparation, tensile testing, dynamic tensile testing, and modal analysis. Three different vibration modes are selected to excite the low frequency modes. The vibroacoustic method is a method based on the propagation of high frequency sound waves in solid structures with low frequency excitation. The trained output signal will be converted from the time domain to the frequency domain supported by the use of MATLAB software. The analysis results show that there is a significant influence on the detection of fatigue cracks in aluminum using the vibration acoustic method. The analyzed data shows that measuring the laser distance will influence the crack detection process. Fatigue cracks can occur because the material is unable to withstand the load applied repeatedly. A nonlinear vibroacoustic method was introduced to overcome this problem. This is because this method is one of the best solutions because it is suitable for detecting fatigue cracks which is sensitive enough to detect small cracks. The aim of the research is to determine the effect of laser distance measurements on fatigue crack detection using the vibroacoustic method. Therefore, there are steps or procedures that include test object preparation, tensile testing, dynamic tensile testing, and modal analysis. Three different vibration modes are selected to excite the low frequency modes. The vibroacoustic method is a method based on the propagation of high frequency sound waves in solid structures with low frequency excitation. The trained output signal will be converted from the time domain to the frequency domain supported by the use of MATLAB software. The analysis results show that there is a significant influence on the detection of fatigue cracks in aluminum using the vibration acoustic method. The analyzed data shows that measuring the laser distance will influence the crack detection process.